1989
DOI: 10.1126/science.2734611
|View full text |Cite
|
Sign up to set email alerts
|

Bright Light Induction of Strong (Type 0) Resetting of the Human Circadian Pacemaker

Abstract: The response of the human circadian pacemaker to light was measured in 45 resetting trials. Each trial consisted of an initial endogenous circadian phase assessment, a three-cycle stimulus which included 5 hours of bright light per cycle, and a final phase assessment. The stimulus induced strong (type 0) resetting, with responses highly dependent on the initial circadian phase of light exposure. The magnitude and direction of the phase shifts were modulated by the timing of exposure to ordinary room light, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
460
1
13

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 848 publications
(496 citation statements)
references
References 48 publications
22
460
1
13
Order By: Relevance
“…The timing of light exposure has a differential effect upon circadian phase: early light exposure advances the cycle whilst light late in the internal day delays circadian phase (Czeisler et al 1989; Khalsa et al 2003). In our student population, we found that longer time spent outside the later chronotype, which would suggest that our population was exposed to more phase delaying evening light than phase advancing morning light.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of light exposure has a differential effect upon circadian phase: early light exposure advances the cycle whilst light late in the internal day delays circadian phase (Czeisler et al 1989; Khalsa et al 2003). In our student population, we found that longer time spent outside the later chronotype, which would suggest that our population was exposed to more phase delaying evening light than phase advancing morning light.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of light exposure has a differential effect upon circadian phase: early light exposure advances the cycle whilst light late in the internal day delays circadian phase (Czeisler et al 1989; Khalsa et al 2003). Thus, exposure to bright artificial light in the evening before bedtime has been associated with a delay in circadian phase, as assessed by measures of subjective chronotype (Martin et al 2012; Vollmer et al 2012), subjective sleep timing (Koo et al 2016), salivary melatonin levels (Gordijn et al 1999; Benloucif et al 2008; Cajochen et al 2011) and core body temperature (Krauchi et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…• Constant routine protocol: To assess intrinsic activity controllers (i.e., circadian or other neural centers) independent of scheduled and random external influences, activity recordings are made in the laboratory throughout 38 h of constant posture (semi-recumbent), wakefulness, environment (21°C, dim light [< 8 lux]), dietary intake and scheduled events [13,14]. This protocol is performed in a subset of subjects (7 males, 4 females) that participated in the daily routine protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Since the resetting trials from which Data set #2 are taken showed type 0 resetting (Czeisler et al 1989), it followed that an appropriate critical stimulus could totally suppress the endogenous rhythm of the circadian pacemaker, and this might be reflected in A , of the temperature rhythm. A total of 18 attempts to reduce A , to zero have been reported (Jewett et al 1991).…”
Section: Data Set #3 Critical Stimulus Testsmentioning
confidence: 99%
“…The five subjects in this set were extensively used in phase resetting trials reported by Czeisler et al (1989). In many instances the phase shifts generated by bright light stimuli were large and, because the phase resetting contour is 'Type 0', probably involved large transient reductions of circadian amplitude (Jewett et al 1991).…”
Section: Data Set #2; Multiple Trial Subjectsmentioning
confidence: 99%